Supply Chain Risks and Uncertainty in the Automotive Industry - Lin, Sung-Chieh (2012)
The aim of this research is to identify supply chain risks and uncertainty in automotive companies and the strategies that can be applied to help automotive companies mitigate risks and uncertainty. The case study method is applied in this research and the approach to progress data collection is through interviews. The case companies chosen for interviews are one automobile manufacturer and two parts suppliers in Taiwan. From the analysis of data collected, factors that cause supply chain risks and uncertainty in the case companies can be identified, besides, the research finds the strategies that can be applied to help automotive companies mitigate risks and uncertainty are categorized to supply chain operation process, cooperative relationship between supply chain members, and information sharing these three aspects. The research also discusses how these strategies can respond to the impacts caused by risk and uncertainty problems effectively, and further achieve the effective integration of supply chain resources and the elevation of performance for the companies.